Reader Interaction with Graphic Devices in Early Modern English Printed Books - Liira, Aino (Wiley, 2025)
Research into marginalia or reader annotations has become a well-established branch of early modern book studies, shedding light on one of the ways in which manuscript and print coexisted and interacted in this period. The present study sets out to discover how readers engaged with printed graphic devices and with texts that contain such devices, and whether the evidence of use indicates that actual readers' needs were aligned with those anticipated by writers and book producers. The study provides a survey of handwritten or handdrawn marks of reader engagement with images, tables, diagrams and other graphic devices in Early Modern English printed books published between 1473 and ca. 1700. The study identifies a ‘core group’ of four types of interaction with graphic devices: modifications or additions to printed graphic devices; whole or partial copies of the devices; handwritten or drawn original devices; and reactive or evaluative comments on the devices. The article shows that while early modern readers often annotated the text more readily than its graphic devices, the different kinds of interaction with graphic devices often indicate active engagement and understanding of the graphic conventions.